2012
DOI: 10.1108/03074801211245002
|View full text |Cite
|
Sign up to set email alerts
|

Rural library services II

Abstract: PurposeThis is the second article focusing on rural library services in Bangladesh. The main aim of this paper is to empirically measure the performance and impact of rural library activities in northern districts of Bangladesh.Design/methodology/approachThe study was carried out separately in ten rural communities with library facilities. Background data about library collections were collected. Point‐of‐exit interviews with library users were carried out to gather their opinion on library collections, perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The effect is more efficient than traditional teaching media and can better enhance the motivation of learners and interests. Ali (2018) compared e-books with paper books and indicated that e-books outperformed paper books on presentation patterns, number of users, sensory learning, material attributes, evaluation feedback, costs, and searchability. Therefore, the application of e-book integrated learning with lively and diverse materials (images and sound effects) could enhance the learning motivation and learning effectiveness of students.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The effect is more efficient than traditional teaching media and can better enhance the motivation of learners and interests. Ali (2018) compared e-books with paper books and indicated that e-books outperformed paper books on presentation patterns, number of users, sensory learning, material attributes, evaluation feedback, costs, and searchability. Therefore, the application of e-book integrated learning with lively and diverse materials (images and sound effects) could enhance the learning motivation and learning effectiveness of students.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Studies have used surveys and questionnaires to assess user satisfaction with library services and their impact on academic work (Mohindra and Kumar, 2015). Point-of-exit interviews have also been conducted to gather users' opinions on library collections, performance and impact (Islam and Ahmed, 2012).…”
Section: The Role Of Libraries In Academic Achievementmentioning
confidence: 99%